2009
DOI: 10.1093/annonc/mdn781
|View full text |Cite
|
Sign up to set email alerts
|

Phase III trial of doxorubicin plus cyclophosphamide (AC), docetaxel, and alternating AC and docetaxel as front-line chemotherapy for metastatic breast cancer: Japan Clinical Oncology Group trial (JCOG9802)

Abstract: Results: A total of 441 patients were entered in a randomized study. Response rates were 30% for AC, 41% for D, and 35% for AC-D. The median times to treatment failure (TTFs) were 6.4, 6.4, and 6.7 months (one-sided log-rank test, P = 0.13 for AC versus D, P = 0.14 for AC versus AC-D) and median overall survival (OS) was 22.6, 25.7, and 25.0 months (P = 0.09 for AC versus D, P = 0.13 for AC versus AC-D) in the AC, D, and AC-D, respectively. Conclusion:There was no difference in the TTF among the three arms. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Thus, TTF does not greatly affect the schedule, and it is available for use as a variable in the real-world clinical settings. In the present study, BP regimen yielded a median TTF of 6.2 months a value that is close to the median TTFs (6.6 and 8.9 months, respectively) which were described in two previous clinical studies in patients with MBC 15,16 .…”
Section: Safetysupporting
confidence: 89%
“…Thus, TTF does not greatly affect the schedule, and it is available for use as a variable in the real-world clinical settings. In the present study, BP regimen yielded a median TTF of 6.2 months a value that is close to the median TTFs (6.6 and 8.9 months, respectively) which were described in two previous clinical studies in patients with MBC 15,16 .…”
Section: Safetysupporting
confidence: 89%
“…The MDS response rate of 23% is only slightly higher and comparable to the response rate in breast cancer at 18%. For further comparison, an objective response rate of 40% in metastatic breast cancer treated with docetaxel has been reported [48]. Also, first-line therapy of metastatic colorectal cancer, the oxaliplatin, infusional fluorour acil and leucovorin (FOLFOX) regimen has been reported as having statistically significant response rates as high as 45% [49].…”
Section: Results N Azacitidine and Decitabine As A Single Agent In Solimentioning
confidence: 99%
“…There was no difference in TTF among the three groups. The researchers concluded that there was a favorable trend in OS for single-agent docetaxel compared with AC in this setting (15).…”
Section: Jcog 9802 Trialmentioning
confidence: 95%
“…In the JCOG 9802 trial (Tables 2 and 3), AC, single-agent docetaxel and alternating AC and docetaxel (AC-D) were compared as first-line chemotherapy in MBC (15). Patients with MBC resistant to endocrine therapy were enrolled in the randomized study to receive either six 3-week cycles of AC (doxorubicin 40 mg/m 2 þ cyclophosphamide 500 mg/ m 2 ), docetaxel (60 mg/m 2 ) or alternating treatment with AC-D (three cycles of AC and three cycles of docetaxel).…”
Section: Jcog 9802 Trialmentioning
confidence: 99%